Self-Starting Characteristics and Flow-Induced Rotation of Single- and Dual-Stage Vertical-Axis Wind Turbines - Muhammad Saif Ullah Khalid; David Wood; Arman Hemmati (Energies, 2022)
Despite offering promising opportunities for wind energy harvesting in urban environments, vertical axis wind turbines face limitations in terms of poor starting characteristics. In this study, we focus on analyzing improvements offered by dual-stage turbines for a range of wind velocities. Numerical simulations are performed for different phase angles between the rotors (a measure of relative angular positions of the blades in the two rotors) to quantify the response time for their starting behavior. These simulations rely on a through sliding mesh technique coupled with flow-induced rotations. We find that for <semantics>U∞=4</semantics><semantics>m/s</semantics>, the phase angles of <semantics>30∘</semantics> and <semantics>90∘</semantics> substantially reduce starting time in comparison to a single-stage turbine. Dual-stage turbines with a phase angle of <semantics>90∘</semantics> exhibit similar or better starting behavior for other wind speeds. The phase angle of <semantics>0∘</semantics> in double-rotor turbines shows the poorest starting response. Moreover, it is revealed that stabilization of shear layers generated by the blades passing through the windward side of the turbine, vortex-entrapment by these rotating blades, and suppressing of flow structures in the middle of the wake enhance the capacity of VAWTs to achieve faster steady angular speed.